Utility of ultrasound as a promising diagnostic tool for stroke-related sarcopenia: A retrospective pilot study. Issue 36 (9th September 2022) - Park, Siha; Kim, Yuntae; Kim, Soo A; Hwang, Insu; Kim, Doh-Eui
Abstract : Stroke patients undergo extensive changes in muscle mass which lead to stroke-related sarcopenia. Stroke-related sarcopenia has a significant impact on the functional outcome of stroke survivors. So, it is important to measure muscle mass in stroke patients. This study aimed to examine the correlation between ultrasonographic quadriceps muscle thickness (QMT) and dual-energy X-ray absorptiometry (DXA) derived appendicular lean mass (ALM) in patients with acute hemiplegic stroke. Twenty five participants were included (13 men and 12 women) in this study, who were diagnosed with stroke within 1 month. For both paretic and non-paretic legs, QMT was measured by an ultrasound and ALM was obtained by performing DXA scan. We analyzed the difference and the correlation between ultrasonographic QMT and DXA-derived lean body mass of both paretic and non-paretic legs. Stroke patients were divided into 2 groups according to the paretic knee extensor power. Ultrasonographic QMT, DXA scan findings, and functional parameters were compared. There was a significant correlation between QMT and ALM index, and between QMT and site-specific lean mass (SSLM) of both the legs for both the sexes ( P < .05). In multivariate linear regression model, we made adjustments for the confounding factors of age, sex, body mass index (BMI) and paretic knee extensor power. We observed a positive relationship between QMT and ALM index ( P < .05), and between QMT and SSLM of both the legs ( P < .05). The % QMT showed higher difference than % SSLM between paretic and non-paretic legs (10.25% vs 4.58%). The QMT measurements of ultrasound show a great relationship with DXA scan findings. Ultrasound better reflects the change of muscle mass between paretic and non-paretic legs than DXA scan at an acute phase of stroke. Ultrasound could be a useful tool to evaluate stroke-related sarcopenia.